Modeling and optimization of lime-based stabilization in high alkaline arsenic-bearing sludges with a central composite design. Issue 5 (16th April 2017) - Lei, Jie; Peng, Bing; Min, Xiaobo; Liang, Yanjie; You, Yang; Chai, Liyuan
ABSTRACT: This study focuses on the modeling and optimization of lime-based stabilization in high alkaline arsenic-bearing sludges (HAABS) and describes the relationship between the arsenic leachate concentration (ALC) and stabilization parameters to develop a prediction model for obtaining the optimal process parameters and conditions. A central composite design (CCD) along with response surface methodology (RSM) was conducted to model and investigate the stabilization process with three independent variables: the Ca/As mole ratio, reaction time and liquid/solid ratio, along with their interactions. The obvious characteristic changes of the HAABS before and after stabilization were verified by X-ray diffraction (XRD), scanning electron microscopy (SEM), particle size distribution (PSD) and the community bureau of reference (BCR) sequential extraction procedure. A prediction model Y(ALC) with a statistically significant P -value <0.01 and high correlation coefficient R 2 = 93.22% was obtained. The optimal parameters were successfully predicted by the model for the minimum ALC of 0.312 mg/L, which was validated with the experimental result (0.306 mg/L). The XRD, SEM and PSD results indicated that crystal calcium arsenate Ca5 (AsO4 )3 OH and Ca4 (OH)2 (AsO4 )2 ·4H2 O formation played an important role in minimizing the ALC. The BCR sequential extraction results demonstrated that the treated HAABS were stable in a weak acidic environment for a short time but posed a potential environmental risk after a long time. The results clearly confirm that the proposed three-factor CCD is an effective approach for modeling the stabilization of HAABS. However, further solidification technology is suggested for use after lime-based stabilization treatment of arsenic-bearing sludges.